Carbene ligand and complex design directed towards application in synthesis and homogeneous catalysis - Stander-Grobler, Elzet (Stellenbosch : Stellenbosch University, 2008)
Thesis (PhD (Chemistry and Polymer Science))--Stellenbosch University, 2008.